PERCEPTIONS OF STIGMA AND DISCRIMINATION IN HEALTH CARE SETTINGS TOWARDS SUB-SAHARAN AFRICAN MIGRANT WOMEN LIVING WITH HIV/AIDS IN BELGIUM: A QUALITATIVE STUDY. Issue 5 (3rd October 2016) - Arrey, Agnes Ebotabe; Bilsen, Johan; Lacor, Patrick; Deschepper, Reginald
Summary: Stigma and discrimination within health care settings remain a public health challenge across diverse cultural environments and may have deleterious effects on mental and physical health. This study explores the causes, forms and consequences of HIV-related stigma and discrimination among migrant sub-Saharan African women living with HIV in Belgium. A qualitative study was conducted with 44 HIV-positive sub-Saharan African migrant women between April 2013 and December 2014 in health care settings in Belgium. Data were analysed using thematic content analysis. Twenty-five of the women reported overt stigma and discrimination and fifteen reported witnessing behaviours that they perceived to be stigmatizing and discriminatory in health care settings. The themes that emerged as to the causes of stigma and discrimination were: public perceptions of migrants and HIV, fear of contamination and institutional policies on HIV management. Reported forms of stigma and discrimination included: delayed or denied care, excessive precautions, blame and humiliation. The consequences of stigma and discrimination were: emotional stress, inconsistent health-care-seeking behaviour and non-disclosure to non-HIV treating personnel. Stigma and discrimination in health care settings towards people with HIV, and more specifically towards HIV-positive sub-Saharan African migrant women, impedes sustainable preventive measures. Specialized education and training programmes for non-HIV health care providers require in-depth investigation.